MILTON BARRAGÁN DUMET E L’ARCHITETTURA MODERNA IN ECUADOR - A. Gritti (2019)
Milton Barragàn Dumet (1934), architect and sculptor, is one of the main protagonists of modern artistic culture in Ecuador. Some of his architectural works, such as the CIESPAL and the Templo de la Patria, have contributed to bring him to the the international scene and to identify him as a figure of reference in the Latin American brutalism. Growing up in Arquin, the first recognized architectural and engineering office in Ecuador, Barragàn Dumet consolidated his training through some long journeys in Europe, followed by numerous commitments in Ecuadorian public institutions at political, professional and academic level. From an European perspective, the critical reflection on the outcomes of its rich intellectual biography helps to restore a broader and more informed outline of the way modern Latin American architecture has absorbed the characteristics of North Atlantic modernity and, therefore, how it has emancipated, thanks also to the rediscovery of its proper roots.